Prediction Efficacy of Prognostic Nutritional Index and Albumin–Bilirubin Grade in Patients With Intrahepatic Cholangiocarcinoma After Radical Resection: A Multi-Institutional Analysis of 535 Patients - Li, Qi; Chen, Chen; Zhang, Jian; Wu, Hong; Qiu, Yinghe; Song, Tianqiang; Mao, Xianhai; He, Yu; Cheng, Zhangjun; Zhai, Wenlong; Li, Jingdong; Zhang, Dong; et al. (Frontiers in Oncology, 2021)
Background: Preoperative nutritional and immunological status have been reported to be independent prognostic factors of patients with intrahepatic cholangiocarcinoma (ICC). This study aimed to investigate whether prognostic nutritional index (PNI) + albumin-bilirubin (ALBI) could be a better predictor than PNI and ALBI alone in patients with ICC after radical resection. Methods: The prognostic prediction evaluation of PNI, ALBI, and PNI + ALBI grade were assessed from 373 patients with ICC who underwent radical resection between 2010 and 2018 at six Chinese tertiary hospitals, and external validation was conducted from 162 patients at other four Chinese tertiary hospitals. Overall survival (OS) and relapse-free survival (RFS) were estimated by Kaplan-Meier method. Multivariate analysis was conducted to identify independent prognostic factors. Time-dependent ROC curve and nomogram prediction model were further constructed to assess the predictive ability of PNI, ALBI, and PNI + ALBI grade. The C-index and calibration plot was used to assess performance of the nomogram model. Results: Univariate analysis showed that PNI, ALBI, and PNI+ALBI grade were prognostic factors for OS and RFS of patients with ICC after radical resection in training set and testing set (P<0.001). Multivariate analysis showed that PNI+ALBI grade was independent risk factors for OS and RFS in training set and testing set (P<0.001). Analysis of the relationship between PNI+ALBI grade and clinicopathological characteristics showed that PNI+ALBI grade correlated with obstructive jaundice, AFP, CA19-9, CA125, PNI, ALBI, Child-Pugh grade, type of resection, tumor size, major vascular invasion, microvascular invasion, T stage and N stage (P<0.05). Time-dependent ROC curves showed that PNI+ALBI grade had better prognostic predictive ability than PNI, ALBI and Child-Pugh grade in training set and testing set. Conclusion: Preoperative PNI+ALBI grade is an effective and practical predictor for OS and RFS of patients with ICC after radical resection.